Travelling light: Fouling biota on macroplastics arriving on beaches of remote Rapa Nui (Easter Island) in the South Pacific Subtropical Gyre. (December 2018) - Rech, Sabine; Thiel, Martin; Borrell Pichs, Yaisel J.; García-Vazquez, Eva
Abstract: Marine anthropogenic debris was sampled from two beaches on the remote South Pacific island Rapa Nui (Easter Island). Abundance, composition, and the attached fouling assemblages on stranded litter were analysed. Most litter (n = 172 items found) was composed of plastic material, and 34% of all litter items were fouled. The main fouling species was the encrusting bryozoan Jellyella eburnea . Transporting vectors were exclusively made from plastics and were mainly small items and fragments, probably stemming from the South Pacific Subtropical Gyre. We present the first report of Planes major, Halobates sericeus, and Pocillopora sp. on anthropogenic litter in the South Pacific. Highlights: Anthropogenic marine litter from the South Pacific Subtropical Gyre strands on Rapa Nui. 34% of all stranded items carried attached biota. Rafts were exclusively made from plastics (mainly small items and fragments). The main fouling species was the encrusting bryozoan Jellyella eburnea . Anthropogenic marine litter transports non-native biota to Rapa Nui.